تقويم برنامج دمج التكنولوجيا بالتعليم من وجهة نظر الطلبة المعلمين وفق بعض المتغيرات دراسة ميدانية في معهد الباسل للمعلوماتية بطرطوس - الياس أسما; الطرابيشي سهام; عرابي حسن محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تقويم برنامج دمج التكنولوجيا بالتعليم من وجهة نظر الطلاب دراسة تقويمية ميدانية في معهد الباسل للمعلوماتية في طرطوس هدفت الدراسة إلى الإجابة عن السؤال الرئيسي الآتي : ما مدى رضا طلبة معهد الباسل للمعلوماتية في مدينة طرطوس عن برنامج دمج التكنولوجيا بالتعليم ؟ استخدم الباحث المنهج الوصفي التحليلي لمناسبته لطبيعة البحث الذي يصف الظاهرة موضوع البحث ثم يفسر ويقارن بغية التوصل إلى التعميمات التي تفيد في تحسين الظاهرة المدروسة وطبقت الدراسة على عينة /191/ طالب وطالبة. توصلت الدراسة إلى نتائج أهمها : 1 ـ يوجد نقاط قوة وضعف في برنامج دمج التكنولوجيا بالتعليم المتبع في معهد الباسل للمعلوماتية من وجهة نظر الطلبة. 2 ـ لا يوجد فرق ذو دلالة احصائية بين متوسطي درجات آراء أفراد عينة البحث نحو البرنامج تعزى إلى متغير التخصص الأكاديمي. 3 ـ لا يوجد فرق ذو دلالة احصائية بين متوسطي درجات آراء أفراد عينة البحث نحو البرنامج تعزى إلى متغير الجنس. وتوصلت الدراسة إلى مجموعة مقترحات أهمها : 1 ـ تحقيق مبدأ التعلَم الذاتي ، والعمل التعاوني لدى المتعلمين من خلال التعامل مع التكنولوجيا . 2 ـ الاهتمام بالمواد التربوية التي تتصل بعمل المدرس الفعلي لطرائق التدريس وتقنيات التعليم وتطويرها في ضوء النماذج الحديثة. 3 ـ الإفادة من تجارب الدول المتقدمة في تطوير العملية التربوية والتعليمية عبر المؤتمرات والندوات التعليمية والتربوية, وربطها بمواقع الإنترنت للاطلاع عليها من قبل أكبر عدد من المدرسين والمتعلمين. Evaluating the program of integrating technology with education according to the students opinions. The study is done at Al-Basel Institute of Informatics in Tartous. The aim of the study is to answer the following main question: How much are the students of Al-Basel Institute satisfied with the program of integrating technology with education? The researcher uses the descriptive, analytic method because it fits the nature of the research, which describes the idea under study and then explains and compares data to reach to generalizations that benefit in improving the phenomenon under study. The study is applied to a sample of /191/ students. The study yielded results, the most important of which are: 1 – According to the students, there are strengths and weaknesses in this program. 2 – There are no statistically significant differences among the average scores of the opinions of the students of the sample regarding the program as to the different academic specializations. 3 – There are no statistically significant differences among the opinions of the students of the sample regarding the program as to gender. The study had a set of suggestions, the most important of which are: 1 – To use the principle of self-education and cooperation among the learners by dealing with technology. 2 – To pay more attention to the educational materials which are related to the actual work of the teacher according to the methods of teaching (methodology), the teaching technology and their improvement and development in the light of modern models. 3 – To benefit from the experiences of the advanced countries to develop the educational and learning process by holding conferences and educational symposiums, and communicating them through websites in order to be read by a large number of teachers and students.